Physical Activity and Skipping Breakfast Have Independent Effects on Body Fatness Among Adolescents - Cayres, Suziane U. [UNESP]; Urban, Jacqueline B. [UNESP]; Fernandes, Romulo A. [UNESP] (Lippincott Williams & Wilkins, 2018)
Objective: We analyzed the longitudinal relationship between breakfast intake and adiposity among adolescents, and the possible mediation role of physical activity on this phenomenon. Methods: We conducted the longitudinal study composed of 86 adolescents (11-14 years old), absence of any known chronic diseases and no regular medicine use that returned the formal consent and assent both signed. Breakfast intake was reported through face-to-face interviews. Adiposity was assessed using a densitometry scanner. Physical activity was estimated through step counts performed using pedometers. Biological maturation was estimated through the maturity level. Student t test for independent samples was used to compare adolescents who were nonskipping breakfast'' and skipping breakfast,'' whereas the relationship between adiposity, physical activity, and skipping breakfast was assessed using Pearson correlation. Structural equation model was created to identify the mediation role of physical activity on the relationship between nonskipping breakfast and adiposity. Results: After 12 months, adolescents who had consumed breakfast regularly presented decreased trunk fatness (-3.5% [95% confidence interval (CI): -6.9 to -0.2]) and body fatness (-2.3% [95% CI: -3.9 to -0.7]) compared with their counterparts. Physical activity had an inverse relationship with trunk fatness (r = -0.270 [95% CI: -0.457 to -0.060]). Nonskipping breakfast was, however, not significantly related to trunk fatness; however, physical activity seems to reduce trunk fatness in our sample (r = -0.281; 95% CI: -0.479 to -0.083). Conclusions: Adolescents who ate breakfast regularly presented lower body fatness independent of physical activity, whereas trunk fatness decreased in adolescents who improved physical activity.
Keywords: health; obesity; pedometer